Analysis of The Efficiency and Effectiveness of Regional Financial Management in Regional Revenue Agencies Southeast Sulawesi Province - Wahyuni Rahmah; Arfin Bagea; Nuzul Ibnu Hajar (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the effectiveness and efficiency of the management of Regional Original Revenue (PAD) in Southeast Sulawesi Province from 2021 to 2023. The analysis results show that the PAD effectiveness ratio for the three years was at an excellent level, with an average of 104.06%, indicating the local government's ability to realize revenues according to or even exceed the set targets. However, there was a decline in effectiveness in 2023, which signals the need to evaluate and adjust PAD management targets and strategies. Meanwhile, the efficiency ratio showed unfavorable conditions, with an average of 165.91%, indicating that PAD collection costs were higher than the revenues obtained, indicating waste and inefficiency in the collection process. Therefore, this study emphasizes the need for serious attention to improve the efficiency of regional financial resource management to reduce collection costs and prevent excessive burdens on the regional budget